Peran Kondisi Sosio-Ekonomi Keluarga terhadap Perencanaan Karir Siswa - Angela Pratama; Nuzmi Sasferi; Farid Imam Kholidin (Institut Agama Islam Negeri Kerinci, Indonesia, 2022)
Several factors influence student career planning. This study aims to describe: 1) socio-economic conditions of the family, 2) career planning, and 3) the role of family socio-economic conditions on students' career planning. This research method uses qualitative research with a case study approach. Research informants are school counselors, students, and parents of Junior High School 4 Sungai Penuh. Data were collected through interviews. The data analysis technique uses Miles dan Huberman data reduction, data display, data conclusion, and verification. The data validity technique uses triangulation. The results of this study revealed that: 1) students continue their education depending on the socio-economic conditions of the family, 2) the career planning of students according to their talents and interests, 3) the socio-economic conditions of the family significantly affect the career planning of students